ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI WAJIB PAJAK MENGENAI PENGGELAPAN PAJAK - Annisa’ul Handayani M; Nur Cahyonowati (Diponegoro Journal of Accounting, 2014)
This research aims to analyze the factors that influence the perception of taxpayers regarding of tax evasion. The independent variable in this research are justice, taxation system, norm, obedience, and discrimination, while its dependent variable of tax evasion. The population in this research was an individual taxpayer listed in Semarang City and the sample in this study used Slovin formula, so that it obtained 400 respondents as samples. In this research, there were 297 respondents that had been analyzed as samples. This analysis used multiple regression analysis. These results indicate that there are several factors that affect the taxpayer's perception regarding of tax evasion, namely justice, taxation system, and obedience